2022
DOI: 10.1111/bju.15842
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training to increase tumour natural killer‐cell infiltration in men with localised prostate cancer: a randomised controlled trial

Abstract: To explore the effects of preoperative high-intensity interval training (HIIT) compared to usual care on tumour natural killer (NK)-cell infiltration in men with localised prostate cancer (PCa), as NK-cell infiltration has been proposed as one of the key mechanisms whereby exercise can modulate human tumours. Patients and MethodsA total of 30 patients with localised PCa undergoing radical prostatectomy (RP) were randomised (2:1) to either preoperative aerobic HIIT four-times weekly (EX; n = 20) or usual care (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Whether the observed effect of acute exercise on NKCA in the circulation translates to cancerous prostate tissue has not been investigated. In a recent study we found no difference in NK cell infiltration into tumor tissue in patients with early-stage prostate cancer randomized to exercise or control ( Djurhuus et al, 2022a , 2022b ). However, we found a positive correlation between the amount of high-intensity training sessions and NK cell infiltration into the tumor tissue indicating a potential dose-dependent relationship ( Djurhuus et al, 2022b ).…”
Section: Discussionmentioning
confidence: 73%
“…Whether the observed effect of acute exercise on NKCA in the circulation translates to cancerous prostate tissue has not been investigated. In a recent study we found no difference in NK cell infiltration into tumor tissue in patients with early-stage prostate cancer randomized to exercise or control ( Djurhuus et al, 2022a , 2022b ). However, we found a positive correlation between the amount of high-intensity training sessions and NK cell infiltration into the tumor tissue indicating a potential dose-dependent relationship ( Djurhuus et al, 2022b ).…”
Section: Discussionmentioning
confidence: 73%
“…From the findings that the acute exercise response in men with prostate cancer is normal, three implications for consideration regarding this type of physical activity are presented. (i) While a single exercise bout was insufficient ( 19 , 48 ), multiple sessions enhanced immune cell infiltration of prostate tumors ( 49 ) that aligns with data from pre-clinical models ( 50 , 51 ). (ii) Breast cancer cell culture experiments reveal that acute but not chronic exercise reduce cell viability ( 52 ), leading to the hypothesis that “every exercise bout matters” ( 53 ).…”
Section: Discussionmentioning
confidence: 68%
“… 227 However, these effects did not translate to humans, as indicated by two randomized controlled trials with prostate cancer patients. 228 , 229 Future studies will have to clarify if these mechanism translate to other tumor entities to elucidate the therapeutic significance of IL-6R signaling in exercise-induced immune cell trafficking.…”
Section: Exerkine-induced Signal Transduction and Biological Tissue A...mentioning
confidence: 99%